2021
DOI: 10.1109/access.2021.3076371
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Wireless Standards in IoT for Indoor Localization Using LoPy

Abstract: There are surplus applications in modern smart cities where localization of indoor environments is critical ranging from surveillance and trailing in smart structures to the localized wireless distribution of advertising content in shopping malls. These applications are only successful if a robust and cost-effective real-time system is developed for precise localization. Another aspect considered for indoor localization is power consumption. Recent wireless standards such as Bluetooth Low Energy (BLE) and LoRa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In [20], the trilateration technique is used to determine the localization accuracy between Wi-Fi, BLE, and Long Range (LoRa) in an indoor environment. The authors concluded that the Wi-Fi had the highest accuracy of 0.54 m. The LoRa had an accuracy of 0.62 m, but their findings were limited to three different environments having a graduate lab of 24 × 24 square feet area, a corridor of 23 × 23 square feet, and a classroom with an area of 50 × 30 square feet.…”
Section: Related Workmentioning
confidence: 99%
“…In [20], the trilateration technique is used to determine the localization accuracy between Wi-Fi, BLE, and Long Range (LoRa) in an indoor environment. The authors concluded that the Wi-Fi had the highest accuracy of 0.54 m. The LoRa had an accuracy of 0.62 m, but their findings were limited to three different environments having a graduate lab of 24 × 24 square feet area, a corridor of 23 × 23 square feet, and a classroom with an area of 50 × 30 square feet.…”
Section: Related Workmentioning
confidence: 99%
“…Several smart factories have emerged by inculcating UWB ( 5 ). Khan et al ( 6 ) defend various wireless technologies, including Wi-Fi and LoRa, to be the most worthy of implementing indoor localization applications because of it being vigorous, affordable, and able to utilize a minimum amount of power.…”
Section: Salient Techniques and Technologies In Indoor Positioning Sy...mentioning
confidence: 99%
“…It is a good choice for Smart Home solutions, which allows users to monitor and reduce energy consumption and control many processes. Nowadays, every smart device (wearables, latest home appliances, consumer electronics) has a built-in Wi-Fi module, which allows for easy and fast communication with other devices that can collect and monitor data [6]. Wi-Fi technology is the most popular and currently the most developed for Smart solutions.…”
Section: Wi-fimentioning
confidence: 99%